A alfabetização matemática na visão de professoras alfabetizadoras de uma escola da rede municipal de ensino de Corumbá, MS - TATIANE ZABALA GOMES (2022)
This dissertation is part of the research line "Educational practices, teacher/educator training in school and non-school spaces" of the Master's Degree Program in Education (PPGE) of the Federal University of Mato Grosso do Sul (UFMS) - Pantanal Campus (CPAN), concentration area in Social Education. Mathematics teaching is an opportunity for literacy and has a significant influence on the student's life, as he begins to analyze contextual situations, becoming a critical thinker in society. This premise leads us to think about the practices of literacy teachers who work in the first three years of the Early Elementary School, raising the following questions: how has the practice of teaching Mathematics been constituted by teachers? What is the view of teachers about the importance of mathematical literacy in the lives of students? To answer these questions, the general objective was to understand the view of teachers who work in classes from 1st to 3rd grade in a school of the municipal education system of Corumbá, MS about mathematical literacy and its influence on teaching practice. The specific objectives consisted of: (i) map what research has pointed out about mathematical literacy; (ii) verify how the understanding of literacy teachers about the teaching of mathematics in literacy classes influences their pedagogical practice; and (iii) identify how teachers treat mathematical content in the literacy context. In a qualitative approach, we conducted interviews with a semi-structured script with four teachers who work from 1st to 3rd grade in a school of the municipal education system of Corumbá, MS. The data was analyzed, taking into account the recurrence and singularities of the participants' statements. It was found that, although the teachers are clear about the importance of mathematical literacy in the social context of the students' lives and understand this phase as important for the whole schooling, there is still a polarization regarding the practice. There is an emphasis on the conception of literacy disconnected from the teaching of mathematics, which directly interferes in the pedagogical practice since they hardly adopt methodologies that boost mathematical literacy. In mapping the research, it was found that the theme began to be addressed more frequently after the effectiveness of the National Pact for Literacy at the Right Age (PNAIC) in schools, with a higher concentration of research from 2015. The influences of the subject Mathematics in the participants' schooling trajectory and the relationship between how mathematical literacy is approached in the classroom were also evidenced. One of the difficulties pointed out refers to the lack of investment by public agencies with continuing education actions, since the study participants explained that the last training on mathematical literacy occurred during the training courses provided by PNAIC in the period between 2014 and 2015. Therefore, it is necessary to seek changes in the way mathematics is taught in the literacy process based on the understanding of its importance in the lives of students.